Internalisasi Karakter Peduli Lingkungan melalui Daur Ulang Limbah Anorganik Dalam Upaya Mendukung program 3R Pemerintah - Tiara Intan Cahyaningtyas; Raras Setyo Retno; Nur Samsiyah (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
Garbage accumulation, especially plastic waste, is a global problem that must be addressed immediately because it will have an impact on the existence of the environment. The purpose of this service program is to support the Government's 3R program in reducing the volume of waste in Indonesia by internalizing the character of caring for the environment while increasing the skills of the Teguhan Village Mentari Garbage Bank management by utilizing plastic waste to make beautiful bags so they are useful. Participants in this service were 32 people consisting of the Management of the Mentari Garbage Bank and members of the Teguhan Mentari Garbage Bank. Community service activities are carried out in the multi-purpose building of Dusun 4 Teguhan village for 3 days, 11-13 December 2022. The service is carried out by arranging permits, recording the number of members of the Mentari Waste Bank and administrators, socializing inorganic waste recycling materials and mentoring and evaluating activities. The results of this community service resulted in a material understanding of the Government's 3R program with quite good achievements with an average of 83%. Knowledge of 3R and the environmental care movement made the participants wiser and more concerned about the environment. The participants received and absorbed training materials on the 3R program and the skills to process inorganic waste properly. Furthermore, the participants can demonstrate directly how to make bags from inorganic waste using certain techniques so that the results obtained can be interesting and of good quality.